Comparison of Anticancer Activities and Biosafety Between Salmonella enterica Serovar Typhimurium ΔppGpp and VNP20009 in a Murine Cancer Model - Liu, Xiaoqing; Guo, Yanxia; Sun, Yujie; Chen, Yu; Tan, Wenzhi; Min, Jung-Joon; Zheng, Jin Hai (Frontiers in Microbiology, 2022)
Salmonella typhimurium strains defective in guanosine 5'-diphosphate-3'-diphosphate synthesis (ppGpp) synthesis (ΔppGpp) is an attenuated strain with good biosafety and excellent anticancer efficacy. It has been applied in preclinical studies of anticancer therapy for various kinds of solid cancers. VNP20009 is another genetically modified nutritionally deficient strain with deletion of purⅠ- and msbB-, which has shown good therapeutic efficacy in various preclinical tumor models and entered phase I clinical trials. Here, the invasion activities and virulence of ΔppGpp was found to be significantly lower than those of VNP20009 strain when tested with cancer cells in vitro. In addition, the MC38 tumor-bearing mice showed equally suppressed cancer growth in average when treated with ΔppGpp or VNP20009 intravenously. However, the ΔppGpp-treated mice showed 16.7% of complete cancer eradication and elongated survival in mice, whereas VNP20009 showed worsened cytotoxicity to animals, even with quite equal tumor size in individual mice. Inflammatory cytokine analysis also showed a decreased level in circulation but strengthened immune boost in tumor microenvironments. Taken together, the engineered ΔppGpp might have greater potential as a cancer therapeutics than VNP20009, and be a promising approach in clinical translation of cancer therapy.